Liposomes for drug delivery: Classification, therapeutic applications, and limitations - Ramachandran Chelliah; Momna Rubab; Selvakumar Vijayalakshmi; Murugan Karuvelan; Kaliyan Barathikannan; Deog-Hwan Oh (Next Nanotechnology, 2025)
Liposomes, lipid-based vesicles, have emerged as a versatile and extensively studied drug delivery platform due to their ability to enhance the therapeutic efficacy of various agents. Over the years, advancements in liposome technology have led to the development and clinical testing of numerous liposome-based drug formulations, with several achieving regulatory approval for medical use. By altering the bio-distribution of therapeutic agents, these formulations have significantly improved their therapeutic indices and minimized off-target effects. This review delves into the current and potential applications of liposomes in drug delivery, highlighting key examples of clinically approved formulations and the challenges faced in their continued development and utilization. A special focus is placed on scalable manufacturing methods, the industrial limitations of liposomal drug products, and regulatory guidelines as defined by the U.S. Food and Drug Administration (FDA) and the European Medicines Agency (EMA). By addressing these critical aspects, this review aims to provide valuable insights for researchers, industry professionals, and regulatory bodies, underscoring the promise and hurdles of liposome-based therapeutics in modern medicine.